Does the Financial Performance of Banks Change During the Global Financial Crisis? The Case of Palestine - Hamed, Wesam M.A.; Faizulayev, Alimshan (Springer Science and Business Media B.V., 2019)
The main goal of this study is empirically evaluating the financial performance of Palestinian banks during the period 2005–2011. The main purpose of these selected periods is to the capture the global financial crisis time effect fully. Both bank-specific and macroeconomic variables are used to investigate the financial performance of banks during the global financial crisis. Fixed-effects and Random-effects methodologies are used to do empirical analysis. The study concluded that the macroeconomic factors have more impact on the profitability of the banks in Palestine, in contrast with bank-specific profitability determinants. © 2019, Springer Nature Switzerland AG.
4th International Conference on Banking and Finance Perspectives, ICBFP 2019 -- 2019-05-02 through 2019-05-03 -- Famagusta -- 273729
Keywords: Banks; Global financial crisis; Inflation; Profitability